P24 WEAREBLE CARDIOVERTER – DEFIBRILLATOR : UTILITY AND USER FRIENDLINESS. (18th May 2022) - Bolognesi, M; Rossi, L; Biagi, A; Coccia, M; Sticozzi, C; Comastri, G; Aschieri, D
Abstract: Background: Worldwide, cardiovascular disease are still a major mode of death, being sudden arrhythmic death (SCD)25 % of total death. Implantable cardioverter defibrillator (ICD) is an effective weapon for SCD prevention in high risk patients with reasonable expectation of survival with good functional status for >1 year. However sometimes the risk of SCD can be transient, so the use of a wearable cardioverter defibrillator (WCD) is considered. Methods: We considered consecutively 40 patients discharged from our cardiology department of Piacenza and Castel san Giovanni that, for potentially transient high risk of SCD, weared a WCD from August 2017 to September 2021, after a systematic education session lasting 30 – 45 minutes. They are followed through remote monitoring. Results: Out of 40 patients, with average age 66 years old and average left ventricular ejection fraction (LVEF) 29%, 88% were males, 70 % suffered from arterial hypertension, 32% diabetes mellitus, 17, 5 % peripheral vascular disease, 35 % chronic renal failure, 55% heart failure, 7, 5% previous stroke. 56% of these patients weared WCD for severe systolic disfunction in ischemic cardiac disease after recent myocardial infarction, after percutaneous coronary intervention or coronary artery bypass graft, 7% after removal of an infected ICD, 9 % whilst awaiting completion of diagnostic tests (chanalopathies/right arrhythmogenic ventricular cardiomyopathy), 34% after newly diagnosed cardiomyopathy.The patients were discharged in high risk mode of SCD with WCD protection.The average wearing time of WCD was 51 days and 22, 98 hours daily. We received 953 trasmissions, with 21 events: 7 ventricular tachicardia, 4 Sopraventricular tachicardia and 5 T wave oversensing .Neither inappropriate shock and neither death were detected .After wearing time and after clinical evaluation, only 52% of patients were subjected to ICD implantation. Conclusions: In our experience we may consider that WCD use is effective, safe and with a good adherence in all patients, considering wearing time. The WCD allows saving resources with less hospitalization time.